Expression of GPX4 by oncolytic vaccinia virus can significantly enhance CD8+T cell function and its impact against pancreatic ductal adenocarcinoma - Wei Wei; Linqing Tian; Xiaoyan Zheng; Lei Zhong; Yuan Chen; Hui Dong; Guibing Zhang; Shibing Wang; Xiangmin Tong (OncoImmunology)
Pancreatic ductal adenocarcinoma (PDAC) is currently difficult to treat, even when therapies are combined with immune checkpoint blockade (ICB). A novel strategy for immunotherapy would be to maximize the therapeutic potential of oncolytic viruses (OVs), which have been proven to engage the regulation of tumor microenvironment (TME) and cause-specific T-cell responses. To boost tumor sensitivity to ICB therapy, this study aimed to investigate how glutathione peroxide 4 (GPX4)-loaded OVs affect CD8+ T cells and repair the immunosuppressive environment. Here, we successfully constructed a novel recombinant oncolytic vaccinia virus (OVV) encoding the mouse GPX4 gene. We found the OVV-GPX4 effectively replicated in tumor cells and prompted the expression of GPX4 in T cells. Our research indicated that OVV-GPX4 could reshape the TME, rectify the depletion of CD8+T cells, and enhance the antitumor effects of ICB therapy.